Pangkalan data perintah-perintah am dan pekeliling Kementerian Pendidikan / Chen Kok Foong - Chen , Kok Foong (2002)
Ministry of Education Malaysia's Web Based Circular Information System (MOE's WBCIS) ajms to enhance the level of searching and_ retrieval of government docunents by providing an effective and faster way of locating circulars on education. In an effort to achieve Vision 2020~ MOE's WBCIS takes the initiative from the implementation of to upgrade the quality of document delivery in and efficient and effective manner. The objectives of MO E's WBCIS, among others, are to help the MOE staffs to manage the circular system easily and fast The system provides an interactive and effective search engine that enables users to search and retrieve education circulars via the net Waterfall methodology has been chosen MOE's WBCIS. The tools used for development the system are Ms Visual Interdev6, Ms Visual Basie, Ms Access, HTML editor. The languages chosen are ASP and visual basic. There are two modules involve in MOE's WBCIS. They are Administrator Module and User Module. User functionality includes search circulars based on keywords (title), circular type and date. This module also let user cancel the search and view the search results. Whereas, authentication (authorized user only can access to database with user name and password), upload, download and modify records of circulars can be found in the Administrator Module. It is expected that with the implementation ofMOE's WBCIS, the system will ease the work of MOE staftS and fully support the Electronic Government initiative towards achieving paperless environment for government documentation.